The Rationality of Ibn Khaldun and Machiavelli In Thought of Religious and Political Relations - Ui Ardaninggar Luhtitianti (Islamic Studies Journal for Social Transformation, 2020)
This article aims to describe Ibn Khaldun and Machiavelli's thoughts in the context of religious and political relations. How are the differences and similarities, and what is the background for their thinking? The method used in this research is descriptive qualitative, with secondary data sources from various literature in the form of books and journal articles that discuss the political, religious, and state thoughts of the two figures. The results of the analysis reveal that Ibn Khaldun and Machiavelli's political, religious, and state thoughts were born as an antithesis to the previous idealistic tendencies of thought. The socio-political situation that developed during their lifetime is one of the causes of these differences in style and significantly influences their thinking. In the context of practical politics, they tend to be rational. Meanwhile, they place religion as an institution that has an essential role as an adhesive element in society. Both of them argue that religion is a social institution that is functional towards the stability of the state.